2004
DOI: 10.1108/02651330410568024
|View full text |Cite
|
Sign up to set email alerts
|

Identifying successful marketing strategies by export regional destination

Abstract: This study develops a model that explains export sales volume by destination based on a company's export marketing strategy. A seemingly unrelated regression model (SURE) simultaneously estimates the explanatory value of the different elements of the marketing strategy, as well as company characteristics, such as experience, size and motivation to export, on entry decisions to six different regional markets made by exporting companies in a southern European country. The data were collected from a sample size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 77 publications
7
73
0
3
Order By: Relevance
“…The positive influence of the adaptation of product strategy confirms Lado et al (2004), Lee and Griffith (2004), and Shoham et al's (2002) results. For the regions they researched, they found a positive influence of this factor.…”
Section: Multiple Regression Analysis With Dependent Factor Of Overalsupporting
confidence: 79%
See 3 more Smart Citations
“…The positive influence of the adaptation of product strategy confirms Lado et al (2004), Lee and Griffith (2004), and Shoham et al's (2002) results. For the regions they researched, they found a positive influence of this factor.…”
Section: Multiple Regression Analysis With Dependent Factor Of Overalsupporting
confidence: 79%
“…The influence of price has been highlighted by various scholars such as Lado et al (2004), Morgan et al (2004), and . However, Sousa and Novello's study (2014) found that there was no influence of the price strategy.…”
Section: Evaluated Internal and Microenvironmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The more committed the firm, the greater is its engagement in planning and the allocation of managerial, financial and human resources to the export venture, which in turn results in a better export venture performance (e.g., Lado, Martínez-Ros, & Valenzuela, 2004;. Thus, we propose the following hypothesis:…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 98%